Understanding the self - Monilla, Ma. Joycelyn A., Go-; Ramirez, Normaliza C. (Quezon City, 2018)
This book specifically discusses the self from various perspectives, explores the different aspects of the self from various perspectives, explores the different aspects of self and identity, and presents the ways of managing and caring for the self
Keywords: Self- perception